2019
DOI: 10.1111/jfbc.13115
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive constituents of Emblica officinalis overcome oxidative stress in mammalian cells by inhibiting hyperoxidation of peroxiredoxins

Abstract: Emblica officinalis (Amla) is a renowned fruit having nutritional and medicinal traits mostly linked to its antioxidants content. In the current study, the methanolic crude extract of amla fruit is subjected to sequential fractionation to get its partially purified fractions. The ethyl acetate (EA) and butanol (BUT) fractions of amla showed maximum antioxidant potential. The ferric reducing capability and nitric oxide scavenging activity were highest in EA fraction. One of the highlights of the study is the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Likewise, IC 50 values of 5.68% w/v (56.8 mg/mL) and 0.87% w/v (8.7 mg/mL) were reported for α-amylase and α-glucosidase in aqueous fractions [36] as compared to 8.22% inhibition at 500 μg/mL and IC 50 value of 70.52 ± 3.65 μg/mL in our study, respectively. Studies have shown that the major constituents like gallic acid, ellagic acid, and quercetin, along with other natural compounds, are responsible for a strong antioxidant effect as well as an antidiabetic effect [46][47][48]. Antioxidative stress activity of these compounds is due to their capability to inhibit the release of malondialdehyde (MDA) from RIN cells along with the reduction in the level of nitric oxide (NO) and glutathione (GSH) that are responsible for mitigating inflammatory responses [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, IC 50 values of 5.68% w/v (56.8 mg/mL) and 0.87% w/v (8.7 mg/mL) were reported for α-amylase and α-glucosidase in aqueous fractions [36] as compared to 8.22% inhibition at 500 μg/mL and IC 50 value of 70.52 ± 3.65 μg/mL in our study, respectively. Studies have shown that the major constituents like gallic acid, ellagic acid, and quercetin, along with other natural compounds, are responsible for a strong antioxidant effect as well as an antidiabetic effect [46][47][48]. Antioxidative stress activity of these compounds is due to their capability to inhibit the release of malondialdehyde (MDA) from RIN cells along with the reduction in the level of nitric oxide (NO) and glutathione (GSH) that are responsible for mitigating inflammatory responses [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants can be synthesized by a cell itself or can be taken exogenously. Antioxidants synthesized by a cell include glutathione, uric acid, caeruloplasmin, ferritin, transferrin, or lactoferrin, whereas vitamin E, vitamin C, flavonoids, and carotenoids come from the diet [ 93 – 95 ]. The endogenous nonenzymatic antioxidants like GSH, uric acid, bilirubin, coenzyme Q, and lipoic acid can be present intracellularly or extracellularly and serve as the primary defence system against imbalanced redox stress [ 96 , 97 ].…”
Section: Therapeutics To Block or Retard The Process: Endothelium mentioning
confidence: 99%
“…ABTS radical scavenging activity of D. oil was measured by the ABTS cation decolorization assay (Chahal et al 2019). The ABTS radicals (ABTS •+ ) were produced by reaction of 7 mM stock solution of ABTS with 2.45 mM potassium persulfate and allowing the mixture to stand in dark at room temperature (25 °C) for 12 h before use.…”
Section: Abts Radical Scavenging Activitymentioning
confidence: 99%